Differences in longer-term smoking abstinence after treatment by specialist or nonspecialist advisors: secondary analysis of data from a relapse prevention trial - Song, F; Maskrey, V; Blyth, A; Brown, T; Barton, G; Aveyard, P; Notley, C; Holland, R; Bachmann, M; Sutton, S; Brandon, T (Oxford University Press, 2015)
Smokers receiving support in specialist centers tend to have a higher short-term quit rate, compared with those receiving support in other settings from professionals for whom smoking cessation is only a part of their work. We investigated the difference in longer-term abstinence after short-term smoking cessation treatment from specialist and nonspecialist smoking cessation services.We conducted a secondary analysis of data from a randomized controlled trial of self-help booklets for the prevention of smoking relapse. The trial included 1088 short-term quitters from specialist stop smoking clinics and 316 from nonspecialist cessation services (such as general practice, pharmacies, and health trainer services). The difference in prolonged smoking abstinence from months 4 to 12 between specialist and nonspecialist services was compared. Multivariable logistic regression analyses were conducted to investigate the association between continuous smoking abstinence and the type of smoking cessation services, adjusted for possible confounding factors (including demographic, socioeconomic, and smoking history variables).The proportion of continuous abstinence from 4 to 12 months was higher in short-term quitters from specialist services compared with those from nonspecialist services (39% vs. 32%; P = .023). After adjusting for a range of participant characteristics and smoking variables, the specialist service was significantly associated with a higher rate of longer-term smoking abstinence (odds ratio: 1.48, 95% CI = 1.09% to 2.00%; P = .011).People who receive support to stop smoking from a specialist appear to be at lower risk of relapse than those receiving support from a nonspecialist advisor.